O patrimônio cultural como patrimônio público: o papel do tribunal de contas na promoção e proteção do patrimônio cultural brasileiro - Nóbrega, Izabel Vicente Izidoro da (2020)
This dissertation aims to analyze the supervisory and pedagogical action of the Courts of Accounts in the promotion and protection of Brazilian cultural heritage, acting positively in the realization of cultural rights inherent to cultural heritage and enabling cultural accountability. The problem to be faced is the questioning of how the Court of Auditors can promote and protect cultural heritage, assisting and collaborating with other bodies that protect cultural heritage. The research started from the hypothesis that the Court of Auditors has its own constitutional competence, established in article 216, § 1, CF / 88, to act in safeguarding and promoting cultural heritage, as well as the duty to cooperate in order to fulfill the SDG Goal 11.4, of Agenda 2030, which determines the implementation of efforts by all Public Administration bodies aimed at safeguarding heritage. With regard to the social and scientific relevance of the research, there was a shortage of legal papers on the subject, so that the present research can contribute to fill this shortage and can be used internationally in all States that adopt the system Court of Auditors. In addition, this research can assist in the discussion about the role of all public bodies, including the Court of Auditors, in the protection and protection of heritage, avoiding irreversible losses of this cultural, social and economic heritage and treasure.